Vitamin D supplementation for depression in older adults: a meta-analysis of randomized controlled trials - Park, Yoonjung; Ah, Young-Mi; Yu, Yun Mi (Frontiers in Nutrition, 2023)
Background: In older adults, depression is associated with several other clinical problems such as cognitive impairment and low quality of life. Several studies have evaluated the relationship between vitamin D and depression in older adults; however, the results have been controversial thus far. Objective: This study aimed to investigate the effects of vitamin D supplementation on depressive symptom improvement among individuals aged ≥ 60 years with or without a diagnosis of depression or depressive symptoms based on a meta-analysis of randomized controlled trials (RCTs). Methods: RCTs were identified to analyze the relationship between vitamin D supplementation and depressive symptoms. MEDLINE, CENTRAL, Embase, and PsycINFO were systematically searched for relevant articles published from inception to November 2022. RCTs that evaluated the effect of vitamin D supplementation in participants aged ≥ 60 years compared to placebo were included. A random effects model was used in this meta-analysis because of the differences between the included RCTs. The quality of the RCTs was assessed using Risk of Bias 2. Results: Seven trials were included in the analyses. The primary outcome of pre-post score changes included five trials with a total of 752 participants. The secondary outcome of post-intervention score included all seven trials with a total of 4,385 participants. No significant improvement in depressive symptoms in either pre-post score changes (standardized mean difference [SMD] = 0.49; 95% confidence interval [CI] -1.07–0.09; p = 0.10) or post-intervention score (SMD = 0.10; 95% CI -0.28–0.07; p = 0.25) was found. Conclusion: Vitamin D supplementation in older adults was not associated with an improvement in depressive symptoms. More studies in older adults are needed to evaluate the association between vitamin D supplementation and depression.